The Correlation Between Self-Confidence and Speaking Ability of Second Semester Students of English Education Study Program at Batanghari University Jambi - Ella Pratiwi Rumapea; Wennyta Wennyta (Universitas Batanghari Jambi, 2020)
The purpose of this study was to find out whether or not there was any correlation between self-confidence and speaking ability of English language learners. The problem of this study referred to the correlation between self-confidence and speaking ability. The study was conducted at the A2 Class of Second Semester Students of English Education Study Program Faculty at Batanghari University Jambi. The population of the study was 15 active students who were studying as the member of a2 class on the second semester students of English Education Study Program Teacher Training and Education Faculty of Batanghari University Jambi in academic year 2019/2020. The sample of this study was all of the A2 class of the second semester students which consist of 15 students with 4 male and 11 female students. The types of the data were quantitative. The data were obtained by using self-confidence questionnaire and speaking test and analyzed by using manual correlation analysis with Pearson Product-Moment formula. Furthermore, it was revealed that r-obtained was (.73) which the researcher concluded that the H0was rejected and H1was accepted. The result concluded that there was a correlation between self-confidence and the speaking ability of the second semester students of English Education Study Program at Batanghari University Jambi.Keywords: Self-confidence, Speaking Ability.